PRODUCTIVE YOUTH EMPOWERMENT MODEL (CASE STUDY AT RUMAH GEMILANG INDONESIA (RGI) LAZNAS AL-AZHAR SAWANGAN-DEPOK) - Kholid Hidayatullah; Bahri Ghazali; Sonhaji Sonhaji; Rosidi Rosidi (Postgraduate State Islamic Institute (IAIN) Metro, 2019)
This study aims to formulate a model of empowering the poor through the Productive Youth empowerment program at Rumah Gemilang Indonesia (RGI) Laznas Al-Azhar. This research was studied qualitatively through a descriptive approach. Data collection methods are done by interview, observation, and documentation. Data analysis uses interactive analysis of the Miles and Huberman models. The model of empowering the poor through the Productive Youth Empowerment program developed in this study refers to the framework of the program evaluation model developed by Kaufman and Thomas (1980). This model was chosen because it places more emphasis on a system, which is an empowerment system that includes inputs, processes, outputs and outcomes. Based on this framework, this study produced a formulation of a model of empowering the poor through the Productive Youth empowerment program as follows: first, empowerment inputs include physical capital, economic capital, human capital, social capital . Second, the process of economic empowerment starts from building spirituality, building entrepreneurial awareness ( leadership and entrepreneurship) , giving capacity (capacity building) to giving power. Third, the empowerment output includes human development, business development, environmental development, and institutional development. Fourth, the empowerment outcome is the economic empowerment of Santri / RGI students as indicated by the formation of skilled workers who have good morality and honest entrepreneurs who are based on strong religious practice, the realization of independence / welfare of students / RGI students characterized by economic strengthening so that there are the transition from mustahik to Muzaaki , business continuity due to the large number of networks built with other institutions , and the availability or ease of access to employment and businesses for self- development